Unleashing the synergistic effect of promising fungicides: a breakthrough solution for combating powdery mildew in pea plants - Maria,; Naz, Ishrat; Khan, Rizwan; Alam, Syed Sartaj; Iqbal, Owais; Akram, Shazia; Rajput, Nasir Ahmed; Younas, Muhammad Usama; Qasim, Muhammad; Ali, Ijaz; Elsalahy, Heba H.; Iqbal, Rashid; et al. (Frontiers in Microbiology, 2024)
Pea powdery mildew, caused by Erysiphe pisi, is a major constraint in pea production worldwide. The emergence of resistant pathogen populations due to frequent and injudicious pesticide use underscores the need to explore synergistic properties of fungicide mixtures. This study investigated the effects of difenoconazole, thiophanate methyl, and sulfur, both individually and in mixtures, on pea powdery mildew, and assessed the interaction types among the selected fungicides. The results demonstrated that the combination of difenoconazole, thiophanate methyl, and sulfur was the most effective, reducing disease severity to 6.10% and minimizing conidia production on foliage. Additionally, this fungicide combination reduced conidial germination by 89.26% in vitro and by 87.50% in a detached leaf assay compared to the control. The treatment also positively impacted leaf chlorophyll content (55.18), green pod yield (22.21 tonnes ha⁻¹), seed yield (12.29 tonnes ha⁻¹), and other yield-related parameters. Although statistically significant, this ternary fungicide combination was closely followed by the binary combination of thiophanate methyl and sulfur, which was the only combination exhibiting synergism in both laboratory and field trials with a synergy factor (SF) > 1. In conclusion, this approach offers improved disease control within integrated disease management (IDM) while minimizing the risk of resistant pathogen strains emerging.